2015
DOI: 10.1016/j.ajog.2015.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic standards for fetal growth: the NICHD Fetal Growth Studies

Abstract: Objective Fetal growth is associated with long-term health yet no appropriate standards exist for the early identification of under- or over-grown fetuses. We sought to develop contemporary fetal growth standards for four self-identified U.S. racial/ethnic groups. Study Design We recruited for prospective follow-up 2,334 healthy women with low-risk, singleton pregnancies from 12 community and perinatal centers between July 2009 and January 2013. The cohort comprised: 614 (26%) non-Hispanic Whites, 611 (26%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
344
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 378 publications
(363 citation statements)
references
References 33 publications
13
344
4
2
Order By: Relevance
“…Given the ethnic differences in EFW reported in the NICHD study 21 and in birthweight data reported herein, combined with the limited number of Caucasian women in our study population, we decided to focus on developing a customized fetal growth standard for African American women. Non-customized centiles (5 th , 10 th , 50 th , 90 th , and 95 th ) of fetal biometric parameters, EFW, and indices of proportionality for all 4,001 African American women (regardless of clinical outcome) are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the ethnic differences in EFW reported in the NICHD study 21 and in birthweight data reported herein, combined with the limited number of Caucasian women in our study population, we decided to focus on developing a customized fetal growth standard for African American women. Non-customized centiles (5 th , 10 th , 50 th , 90 th , and 95 th ) of fetal biometric parameters, EFW, and indices of proportionality for all 4,001 African American women (regardless of clinical outcome) are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting population-level centiles (i.e. non-customized and representing the entire study population) were superimposed on the raw data for visualization purposes and compared to other non-customized standards, such as the NICHD African American standard 21 and the WHO standard non-customized by fetal sex.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations